2020
DOI: 10.7762/cnr.2020.9.3.213
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Nutrition and Inadequate Gestational Weight Gain in Relation to Birth Weight: Results from a Prospective Cohort Study in India

Abstract: Inadequate/excessive gestational weight gain (GWG) can cause adverse pregnancy outcomes and only few studies have described patterns of weight gain in Indian women. Also, studies pertaining to dietary intake throughout gestation are insufficient. This prospective cohort study was conducted to evaluate GWG and nutrient intake in all trimesters of pregnancy and investigate the relationship between themselves along with that of birth weight (BW). Our study was carried out in a population-based prospective birth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
(35 reference statements)
0
9
1
Order By: Relevance
“…The older or non‐first‐time pregnant mothers may have more regular lifestyle preferences and therefore have less weight gain, 18 but in the present study, they have higher pre‐pregnancy weight, probably owing to aging or child‐rearing habits. Besides, some studies have also shown that overweight or obese women were more likely to have excessive GWG, 13,18 which is different from our study and other research 12,23,24 …”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The older or non‐first‐time pregnant mothers may have more regular lifestyle preferences and therefore have less weight gain, 18 but in the present study, they have higher pre‐pregnancy weight, probably owing to aging or child‐rearing habits. Besides, some studies have also shown that overweight or obese women were more likely to have excessive GWG, 13,18 which is different from our study and other research 12,23,24 …”
Section: Discussioncontrasting
confidence: 99%
“…Besides, some studies have also shown that overweight or obese women were more likely to have excessive GWG, 13,18 which is different from our study and other research. 12,23,24 This may be because the majority of women (59.1%) in this cohort have given birth before and so have gained adequate experience and knowledge of GWG, which helps to reach the suggested GWG in the next pregnancy. Our findings imply that nutrition education to avoid immoderate GWG should be initiated as early as possible, especially among younger or first-time pregnant women, housewives, and overweight/obese women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations